Contemporary mexican politics - Edmonds-Poli, Emily 1970-; Shirk, David A. 1971- (Lanham Rowman & Littlefield, 2016)
Now in a thoroughly updated edition, this comprehensive and engaging text explores contemporary Mexico's political development and examines the most important policy issues facing Mexico in the twenty-first century.
Part I. Mexican political development -- Part II. Political institutions, culture, and society -- Part III. Key domestic policy issues -- Part IV. Mexican foreign relations -- Conclusion -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Mexico -- Politics and government -- 2000-.